PERANCANGAN PENGGUNAAN FIREWALL DAN PROXY SERVER UNTUK MEMBATASI HAK AKSES INTERNET - Nana Suryana (Sekolah Tinggi Teknik - PLN, 2018)
The development of computer technology and information is very fast, especially on the provision of computer networks become very important for institutions especially Vocational High School, Institute and University. However, the impact of the development of information technology in line with the rising problems that can be arise such as : attacks on viruses, spam, spyware and others. In addresing the issue, the presence of pornographic sites and others can lower morale, especially for students, due to easy access of the internet. In this case it is also possible that the performance of lecturers and staff in using information systems and learning proses will be destroyed and can reduce the performance of the computer network. Firewall using iptables on proxy server and uses Squid Proxy with Ubuntu Linux Server that has been implemented in the Laboratory. Also can be used for various access to access computer network. With the fastest speed of internet access, then the access sites that are not useful for students and lectures will be block so the do not have access and make the security of the network more secure.